The Verification of a Distributed System. - MCCAFFREY, CAITIE (Communications of the ACM, 2016)
The article discusses the verification and validation of distributed systems. Particular focus is given to partial failure and asynchrony. Details on formal specification languages such as TLA+ and Coq, and on the formal verification method known as model checking, are presented. Informal methods such as monitoring, canary tests, and unit and integration tests are also discussed, along with random model checkers and fault-injection testing.